High isolated defected ground structure based elliptical shape dual element MIMO antenna for S-band applications - Al Gburi, Ahmed Jamal Abdullah; Kumar, Praveen; K. Singh, Ajit; Kumar, Ranjeet; Sinha, Rashmi; K. Mahto, Santosh; Choubey, Arvind (Electromagnetics Academy, 2024)
This research suggests a compact, wideband Multiple Input Multiple Output (MIMO) antenna designed for S-band applications, emphasizing high isolation between closely positioned antenna elements. Achieving this isolation is accomplished through the implementation of a Defected Ground Structure (DGS) technique. The DGS is realized by etching two elliptical patterns on an economical FR-4 substrate with inherent loss properties. Three rectangular slots and two L-shaped stubs are introduced to improve isolation and minimize the size of antenna increment by lowering surface wave propagation. To validate the proposed layout, a physical prototype was constructed for a direct comparison of its performance with the simulated parameters. The results demonstrated highly favorable outcomes, including Diversity Gain (DG) exceeding 9.97 dB, Envelope Correlation Coefficient (ECC) registering below 0.05, Mean Effective Gain (MEG) lower than -3 dB, Total Active Reflection Coefficient (TARC) below 0.4, and Channel Capacity Loss (CCL) less than 0.3. Furthermore, the current distribution and radiation pattern were found to be highly suitable for applications in the S-band and the lower part of the C-band, encompassing technologies like Bluetooth, WiFi, WiMAX, 4G, and 5G.